Correlation of NOD2 genotypes with Helicobacter pylori infection in a South‐European country. Issue 3 (9th July 2020) - de Almeida, Nuno Miguel; Fernandes, Alexandra; Romãozinho, José Manuel; Freire, Paulo; Donato, Maria M.; Cardoso, Olga; Luxo, Cristina; Cipriano, Maria Augusta; Marinho, Carol; Calhau, Carlos; Figueiredo, Pedro
Abstract: Outcome of Helicobacter pylori ( H. pylori ) infection in a specific individual is unpredictable and results from interaction of multiple variables, including host genetic factors. This study aimed to investigate if NOD2 mutations increased the risk of H. pylori infection and if it has any relationship with bacterial genotype or gastric histopathological modifications. This prospective study involved 86 patients (54 females; mean age, 48.7 ± 13.6 years) with positive 13 C‐urea breath test (UBT) and a sex and age‐matched control group of 266 individuals, 64 of them with negative UBT. The three main NOD2 mutations (L1007fsinsC, R702W, and G908R) were obtained for all patients and controls. Fifty‐one infected patients were submitted to endoscopy with gastric biopsies. H. pylori was isolated, and genotypes were determined by PCR. Histopathological features were graded according to the updated Sydney system. Overall, NOD2 mutations were found in 14 patients (16.3%) and in 31 controls (11.7%) (OR = 1.40, 95% CI = 0.78‐2.50; P = .264). Genotype frequencies for L1007fsinsC (1.2% vs 0.8%), R702W (11.6% vs 7.6%) and G908R (5.8% vs 3.4%) were not statistically different between the two groups. A significant positive association was observed between NOD2 polymorphisms and peptic ulcer but only in univariate analysis. There were no other correlations with clinical variables, gastric histological patterns and H. pylori genotypes. NOD2 mutations are not associated with increased prevalence of H. pylori infection or more severe gastric histopathological modifications induced by this bacterium. However, such host polymorphisms could influence clinical manifestations.